2018
DOI: 10.5114/aoms.2016.60718
|View full text |Cite
|
Sign up to set email alerts
|

What does the Cantril Ladder measure in adolescence?

Abstract: IntroductionThe Cantril Scale (CS) is a simple visual scale which makes it possible to assess general life satisfaction. The result may depend on the health, living, and studying conditions, and quality of social relations. The objective of this study is to identify key factors influencing the CS score in Polish adolescents.Material and methodsThe survey comprised 1,423 parent-child pairs (54% girls; age range: 10–17; 67.3% urban inhabitants; 89.4% of parents were mothers). Linear and logistic models were esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 24 publications
4
85
0
Order By: Relevance
“…Mazur and colleagues (2018) studied key factors related to the Cantril Ladder in a Polish sample of adolescents and concluded that the Cantril Ladder can be considered a useful measurement tool for adolescent psychosocial health. They applied two different cut-off points on the scale, and found that moods and emotions showed stronger associations with the traditional cut-off point of 0-5 (low) vs. 6-10 (high) on the Cantril Ladder, while school environment was a stronger associated factor when using a cut-off point of 0-8 (low) and 9-10 (high) (Mazur, Szkultecka-Debek, Dzielska, Drozd, & Malkowska-Szkutnik, 2018). They found that compared to the youngest age group (11-year-olds) life satisfaction was lower among the oldest age group (15-year-olds), while gender differences were small and insignificant.…”
Section: Introductionmentioning
confidence: 99%
“…Mazur and colleagues (2018) studied key factors related to the Cantril Ladder in a Polish sample of adolescents and concluded that the Cantril Ladder can be considered a useful measurement tool for adolescent psychosocial health. They applied two different cut-off points on the scale, and found that moods and emotions showed stronger associations with the traditional cut-off point of 0-5 (low) vs. 6-10 (high) on the Cantril Ladder, while school environment was a stronger associated factor when using a cut-off point of 0-8 (low) and 9-10 (high) (Mazur, Szkultecka-Debek, Dzielska, Drozd, & Malkowska-Szkutnik, 2018). They found that compared to the youngest age group (11-year-olds) life satisfaction was lower among the oldest age group (15-year-olds), while gender differences were small and insignificant.…”
Section: Introductionmentioning
confidence: 99%
“…Life satisfaction was measured by the Cantril ladder, a simple and validated instrument to assess general life satisfaction [29,30]. The students were presented with a vertical visual scale (ladder) ranging from 0 to 10, with the following statement: "How are you currently doing?…”
Section: Methodsmentioning
confidence: 99%
“…Life satisfaction was measured by a single, self-reported indicator, the Cantril Ladder. This instrument, has shown to be an appropriate measurement tool as a wide approach to psychosocial adolescent health [29,30]. The measurement of school climate is also based on self-report by the adolescents.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…FAS is a useful tool in many national and international studies [22,23]. Many authors also indicate the regularity that the lifestyle and behavior of parents with a worse economic situation does not serve the health of their children, e.g.…”
Section: Discussionmentioning
confidence: 99%